2015
DOI: 10.1088/0004-637x/808/1/37
|View full text |Cite
|
Sign up to set email alerts
|

SURVEYING GALAXY PROTO-CLUSTERS IN EMISSION: A LARGE-SCALE STRUCTURE ATz= 2.44 AND THE OUTLOOK FOR HETDEX

Abstract: Galaxy proto-clusters at z 2 provide a direct probe of the rapid mass assembly and galaxy growth of present day massive clusters. Because of the need of precise galaxy redshifts for density mapping and the prevalence of star formation before quenching, nearly all the proto-clusters known to date were confirmed by spectroscopy of galaxies with strong emission lines. Therefore, large emission-line galaxy surveys provide an efficient way to identify proto-clusters directly. Here we report the discovery of a large… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
99
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 83 publications
(106 citation statements)
references
References 157 publications
(222 reference statements)
7
99
0
Order By: Relevance
“…Based on the spatial and redshift distribution traced by zCOSMOS SFGs and the population of DSFGs, it is possible that the large-scale structure associated with the ZFIRE cluster may extend beyond the ZFIRE survey area. In fact, Chiang et al (2015) also detect three LAEs a few arcmins offset from the ZFIRE cluster (their positions are also shown in Figure 2). Such a large spatial extent traced by these various galaxies is consistent with the cosmological simulations (e.g., Chiang et al 2013), where thez 2.1 cluster may still be actively accreting from large-scale structure while more mature cluster cores begin to assemble in the densest regions.…”
Section: Distribution Of Sfgs and Rare Sourcesmentioning
confidence: 78%
See 1 more Smart Citation
“…Based on the spatial and redshift distribution traced by zCOSMOS SFGs and the population of DSFGs, it is possible that the large-scale structure associated with the ZFIRE cluster may extend beyond the ZFIRE survey area. In fact, Chiang et al (2015) also detect three LAEs a few arcmins offset from the ZFIRE cluster (their positions are also shown in Figure 2). Such a large spatial extent traced by these various galaxies is consistent with the cosmological simulations (e.g., Chiang et al 2013), where thez 2.1 cluster may still be actively accreting from large-scale structure while more mature cluster cores begin to assemble in the densest regions.…”
Section: Distribution Of Sfgs and Rare Sourcesmentioning
confidence: 78%
“…Red circles show galaxies with L IR  10 12 L e , and blue boxes indicate X-ray sources. Purple diamonds show the positions of three LAEs from Chiang et al (2015). Brown crosses mark the group candidates identified by Diener et al (2013).…”
Section: * and Sfrmentioning
confidence: 99%
“…0 3 z ( ) s + » and <10% catastrophic failure rate. This target selection process was carried out in 2014 February, prior to the publications by Diener et al (2015) and Chiang et al (2015) reporting galaxy overdensities in the field. We observed these targets with the LRIS DoubleSpectrograph (Oke et al 1995;Steidel et al 2004) on the Keck I telescope at Maunakea, Hawai'i, during 2014 March 26-27/29-30 and April 18-20, using multi-object slitmasks.…”
Section: Observationsmentioning
confidence: 99%
“…Two other developments in the past year lend additional synergy: (i) the first data release of the MOSDEF survey (Kriek et al 2015, hereafter K15), whose near-infrared (NIR) nebular line redshifts reduce systemic redshift uncertainties hence allowing a cleaner comparison with our tomographic map; and (ii) the discovery of a z=2.45 galaxy protocluster within our target field (Diener et al 2015;hereafter D15;Chiang et al 2015; hereafter C15).…”
Section: Introductionmentioning
confidence: 99%
“…In the COSMOS field the two most prominent peaks in the VUDS-DR1 N(z) are at z ∼ 2.45 and z ∼ 2.9. The strong over-density at z ∼ 2.45 was recently pointed out by Chiang et al (2015) and identified by Casey et al (2015) as a proto-cluster including seven star-bursting submillimeterluminous galaxies and five AGN. In the CANDELS-COSMOS area alone we find 22 galaxies with 2.45 ≤ z spec ≤ 2.5.…”
Section: Redshift Distributionmentioning
confidence: 72%